2017
DOI: 10.1016/j.jff.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetric evaluation of a multi-strain probiotic: Interspecies inhibition between probiotic strains

Abstract: 17Lactobacillus plantarum, Lactobacillus rhamnosus, Lactobacillus acidophilus 18and Enterococcus faecium, which are the component species of a 19 commercially available probiotic mixture (Symprove ® , P1), were grown in co-20 culture to determine whether they would inhibit each other in vitro using an 21 isothermal microcalorimeter (IMC). The growth profiles in the IMC were 22 characteristic and unique to each species while the growth profile of P1 was 23 most similar to that of L. plantarum, suggesting this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This has prompted their use in dietary supplements, detoxification therapy, and biotechnology [56,57]. They have shown significant efficacy in stimulating the immune system and function [58], competing against other microorganisms for nutrients, performing bactericidal and antibacterial activity, and competing on the adherence site for space [54]. Their performance is, perhaps, more consistent and efficient [39,59].…”
Section: Advent Of Combining Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has prompted their use in dietary supplements, detoxification therapy, and biotechnology [56,57]. They have shown significant efficacy in stimulating the immune system and function [58], competing against other microorganisms for nutrients, performing bactericidal and antibacterial activity, and competing on the adherence site for space [54]. Their performance is, perhaps, more consistent and efficient [39,59].…”
Section: Advent Of Combining Microorganismsmentioning
confidence: 99%
“…For example, there have been reports of no effect on broiler breeder performance, gastrointestinal tract function, cholesterol concentrations, cell-mediated immunity, malondialdehyde, serum glutathione peroxidase activity, and blood hematology with certain probiotic mixtures containing a dose of 2.5 × 10 7 CFU/g Bifidobacterium thermophilum, Lactobacillus casei, Lactobacillus acidophilus, and Enterococcus faecium [83,97]. Nevertheless, their effectiveness is yet preferred compared to their single strain counterpart [58]. The role played by dosage in their efficacy cannot be overemphasized.…”
Section: Multistrain Probiotic Use In Poultrymentioning
confidence: 99%
“…However, increasing knowledge of probiotics has clearly shown that co-cultures of probiotics can achieve better fermentation and beneficial effects. 7 When L. acidophilus , Lacticaseibacillus rhamnosus , and Pediococcus acidilactici were mixed in culture, an increase in bacterial concentration was observed, which may be due to positive interactions between the co-cultured strains of LAB leading to the synergistic effect of the strains. 8,9 Studies have found that co-cultures can increase the degradation of substrates, thereby increasing the content of peptides, amino acids, and organic acids in the metabolic pathways of the strains.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, prompting their application in biotechnology, detoxification therapy, and as dietary supplements [ 20 , 22 ]. The increased in the use of multi-strain probiotics has revealed optimal effects compared to single-strain probiotics [ 23 ]. However, despite the availability of multi-strain probiotics, not all had shown superior benefits [ 17 ], but overall, their effectiveness compared to single-strain probiotics are preferred [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased in the use of multi-strain probiotics has revealed optimal effects compared to single-strain probiotics [ 23 ]. However, despite the availability of multi-strain probiotics, not all had shown superior benefits [ 17 ], but overall, their effectiveness compared to single-strain probiotics are preferred [ 23 ]. Some multi-strain probiotics are more consistent in their actions than single-strain probiotics [ 15 ].…”
Section: Introductionmentioning
confidence: 99%